In This Issue - Michael Scriven (The Evaluation Center at Western Michigan University, 2005)
This is a particularly interesting issue, which is just as well since it's also our longest to date-over 220 pages, and I doubt you can find a way to shorten it without a hundred readers feeling seriously deprived!